2022
DOI: 10.1007/s10639-022-11346-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of factors affecting transactional distance in E-learning environment with artificial neural networks

Abstract: In this study, the factors affecting the transactional distance levels of university students who continue their courses with distance education in the 2020–2021 academic years due to the Covid pandemic process were examined. Factors that affect transactional distance are modeled with Artificial Neural Networks, one of the data mining methods. Research data were collected from a total of 1638 students, 546 males and 1092 females, studying at various universities in Turkey, by using the personal information for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Due to its potential to increase the effectiveness of educational processes, the integration of the IoT in the higher education [39] sector has recently attracted a lot of interest [40]. The incorporation of the IoT in the e-learning environment [41] has shown promising results in improving learning outcomes and catering to individual learning styles [42]. Learning styles are the varied approaches people use to study and retain knowledge.…”
Section: Overview Of the Iot And E-learning In Heismentioning
confidence: 99%
“…Due to its potential to increase the effectiveness of educational processes, the integration of the IoT in the higher education [39] sector has recently attracted a lot of interest [40]. The incorporation of the IoT in the e-learning environment [41] has shown promising results in improving learning outcomes and catering to individual learning styles [42]. Learning styles are the varied approaches people use to study and retain knowledge.…”
Section: Overview Of the Iot And E-learning In Heismentioning
confidence: 99%
“…This research was conducted through a relational survey model. As long as the interaction between multiple variables is important in social sience, the relational survey model was used (Özbey & Kayri, 2022). As mentioned in previous studies (Del Rincon et al, 2003;Lew et al, 2019;Sánchez & Karaksha, 2022), survey-based method are frequently used in the field of education perhaps owing to the evident ease and openness of this method.…”
Section: Data Collectionmentioning
confidence: 99%
“…Özbey and Kayri [9] proposed multilayer perceptron and radial-based function ANN methods to model the factors that affect transactional distance levels of university students who continued distance learning due to the COVID-19 pandemic. The authors collected research data from more than thousand students from various universities in Turkey and the results showed that multilayer perceptron ANN method provides better results compared to other ANN methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Motivated by the initial successes in transferring knowledge through an Internet model based on a website, teachers developed the idea of improving the quality of the adopted knowledge led by the experience of earlier research related to the creating of various solutions through ANN (Artificial Neural Network) [2][3][4][5][6][7][8][9][10]. This experience was avant-garde, but it provided great opportunities, and, due to the positive feedback in the educational community, an increasing number of professors from various universities and faculties commenced to apply this novel solution to their subjects.…”
Section: Introductionmentioning
confidence: 99%